An Unusual Case of Spontaneous Bladder Perforation with Associated Autodialysis of the Ensuing Urinary Ascites. (16th November 2011) - Aber, A.; Hyder, S. A.; Arumuham, V.
Abstract : Spontaneous rupture of the urinary bladder is a rare occurrence, and when encountered it is a diagnostic challenge. We present an unusual case of urinary bladder rupture in a patient with severe cerebral palsy who initially presented with localized abdominal pain and during admission developed generalized peritonitis caused by bladder rupture. In this case, the patient had none of risk factors associated with urinary bladder.